An Evaluation and Improvement Program for Inpatient Anticoagulant Control - Phillips, W S; Smith, J; Greaves, M; Preston, F E; Channer, K S (Thrombosis and Haemostasis, 1997)
To improve the management and therapeutic control of inpatients on anticoagulant drugs, combined prescription and monitoring charts have been developed for both heparin and warfarin which incorporate clinical guidelines. These have been introduced throughout a 700-bedded acute teaching hospital via a structured program of change management.We have demonstrated improvements in the quality of anticoagulant control (assessed with a custom-written computer program), adherence to clinical guidelines and quality of monitoring and prescribing of anticoagulants in inpatients.The percentage time spent under-anticoagulated with heparin (activated partial thromboplastin time ratio <1.5) fell from 32.7% to 18.5% (p<0.0001), whereas there was no change in percentage time over-anticoagulated (5.1% vs. 5.8%; p = ns). The percentage time spent under-anticoagulated with warfarin was unaltered (26.3% vs. 29.8%; p = ns) but the percentage time spent over-anticoagulated (International Normalised Ratio >4.5) was halved from 5.4% to 2.7% (p<0.001).We conclude that the introduction of the charts led to significant improvements in anticoagulant control.